Can the ketogenic diet improve our dreams? Effect of very low-calorie ketogenic diet (VLCKD) on sleep quality - Luigi Barrea; Ludovica Verde; Cherubino Di Lorenzo; Silvia Savastano; Annamaria Colao; Giovanna Muscogiuri (Journal of Translational Medicine, 2023)
Abstract Background Obesity is a condition that is often associated with sleep disorders, including reduced sleep quality (SQ). Very low calorie ketogenic diet (VLCKD) has proven to be effective in the management of obesity and associated metabolic disorders. However, little is still known about the effects of this promising nutritional protocol on SQ. Thus, the purpose of this study was to investigate the short-term effect of VLCKD on SQ in women with overweight/obesity and if any changes, to identify the predictive factor that through VLCKD modified SQ. Methods Were consecutively enrolled a total of 324 subjects, who met the inclusion criteria and accepted to adhere to VLCKD. Assessment of nutritional status, including anthropometric measurements (height, weight, and waist circumference), bioelectrical impedance analysis (phase-sensitive system, 50 kHz BIA 101 RJL, Akern Bioresearch, Florence, Italy Akern), high sensitivity C reactive protein levels (hs-CRP), and SQ were carried out at baseline and after 31 days of active stage of VLCKD. SQ was evaluated using the validated questionnaire Pittsburgh Sleep Quality Index (PSQI). Results In addition to the expected general improvement of anthropometric parameters and body composition, VLCKD improved significantly SQ, as demonstrated by the improvement of all parameters included in the PSQI questionnaire (p < 0.001). Both at baseline and after 31 days of active stage of VLCKD, the PSQI score was significantly associated with BMI, waist circumference, fat mass, fat free mass (p < 0.001 for all) and hs-CRP (p = 0.023). PhA was negatively associated with PSQI score only at baseline (p < 0.001). ∆% PSQI positively correlated with ∆% BMI, ∆% fat mass, ∆% hs-CRP (p < 0.001 for all) and negatively correlated with ∆% fat free mass (p < 0.001), and ∆% PhA (p = 0.031). In the multiple regression analysis ∆% fat mass represented the only predictor of changes in SQ after VLCKD. Finally, in the ROC analysis, a threshold value of ∆% fat mass > − 8.4% predicted improvement in SQ (p < 0.001). Conclusion In conclusion, VLCKD determines an improvement of SQ in women with overweight and obesity, that was mostly mediated by the reduction of fat mass related to this nutritional protocol. Graphical Abstract